ANALISIS PERFORMANCE LEVEL SENDI PLASTIS LOKAL PADA FONDASI TIANG TUNGGAL DAN TIANG KELOMPOK - Willy Ericson; Hendy Wijaya; Amelia Yuwono (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2020)
Foundation is part of the structure that was build first and the most important part to guarantee the establishment of a building. The foundation function in general are to carry and distribute building loads into the ground. The loads channeled into the ground in the form of axial loads and lateral loads. Generally for high buildings used in the form of foundation piles or bored piles. To find out the design capabilities of a building in maintaining its robustness, naturally some analysis of the lower and upper structures needed. Especially in the lower structure, which is the foundation of a single pile or a group of piles, one of which can be done is a pushover analysis of the pile. By conducting pushover analysis on a pile foundation, the level of performance of the single pile foundation and group pile can be determined. From the results of pole pushover analysis will be obtain including the maximum deflection value and the melting value of pole. From the two data, it can be seen the value of the ductility of various types of pile foundation materials used. In this case, this journal will calculate the ductility and overstrength of a single pile foundation and group pile with variation dimensions.